The Dynamics of Export Specialisation in the Regions of the Italian Mezzogiorno: Persistence and Change - Simona Iammarino; Paolo Guerrieri (European Regional Science Association (ERSA), 2003)
Within the European arena, the heterogeneity of socio-economic conditions among Italian regions is a clear example of intra-border imbalances. Though, the different degree of development characterising the various areas of Italy is far from being an exception in the Union, where diversity across member states is a reflection of domestic socio-economic disparities strongly concentrated in space and reproduced over time. In the most recent years, the pattern of economic growth of the Italian Mezzogiorno has undergone a significant transformation. Up to the beginning of the 1990s, the whole area was by and large characterised by a single macroeconomic model of income and employment, whose dynamics were strongly based upon State intervention. By the early 1990s, the end of the special public support for the Mezzogiorno – as a consequence, to a large extent, of the completion of the Single European Market in 1992 – was only partially followed by appropriate legislative tools for the support of less favoured areas. Since then, the Italian southern regions as a whole have gone through a worsening of their economic fundamentals, particularly with regard to income growth and unemployment. At the same time, the differentials in the patterns of socio-economic development within the southern area have been strengthening, confirming the existence of “many Mezzogiorni” pointed out by the southern literature. In our previous work we have provided further empirical support to the fact that the Italian periphery is far from being a clear-cut and homogeneous set of local contexts, even within the same administrative region. As a consequence, a categorisation without distinctions at the level of policy strategies would imply the agreement on a single “logic of development”, which has indeed already demonstrated its calamitous effects in the application of a “top-down” indistinct industrialisation strategy to the Italian Mezzogiorno. Our current research line aims at providing the basis for devising a policy framework within which trying to identify new directions to untangle regional “vulnerability”, with particular reference to the dramatic changes imposed by internationalisation and globalisation processes. The objective of the present paper is to investigate to what extent the evolution of export patterns and performance by Mezzogiorno province fits in the picture of growing differentiation highlighted in our previous work and in the southern economic literature. Thus, the combined significance of cumulativeness and gradual change in specialisation patterns is examined by testing the extent of continuity in the sectoral composition of trade specialisation profiles by province during the period 1985-2000 (corresponding to the achievement of the single European market and currency). The export performance and the models of specialisation seem to bear out the view of “many Mezzogiorni” and show that peripheral regions and provinces have adopted rather distinct strategies to adjust to the rapidly increasing global economic integration. Our results – on the basis of which a taxonomy of trade specialisation patterns has been devised – stress the difficulty to identify a single “successful path”, that is, cumulativeness versus change in the evolution of provincial specialisation profiles. Rather, it appears to emerge that both (or none) can be successful depending on socio-economic conditions characterising the local contexts of reference even belonging to the same area or region.
Keywords: 330